From BBC radio personality to online audience personae: the relevance of fan studies to Terry Wogan and the TOGs. - Hills, Matt (Radio Journal: International Studies in Broadcast & Audio Media, 2009)
This article suggests that radio studies and fan studies can, and should, be encouraged into meaningful dialogue. It argues that there is a general reason for this, to address the notable absence of work in the field on ‘radio fandom’, and a specific media-technological reason; the role of media convergence in making a wider range of fans more culturally visible, and ever more important to media industries, radio included. It takes Sir Terry Wogan (STW) and the unofficial online community of ‘Terry's Old Gals or Geezers’ (TOGs) as its case study, partly because BBC Radio 2 and its audiences have been academically under-represented in favour of work on ‘cool’ or ‘cultural’ networks such as R1 and R4. This piece argues that www.togs.org can be analysed as a site for ‘off-brand sociability’ with listeners rarely referring to Sir Terry Wogan or Wake up to Wogan, sometimes even playfully denying knowledge of them. However, following developments in fan studies, it is argued that an emphasis on symbolic performances of self, rather than on explicit textual interpretations, can demonstrate how TOGs self-reflectively draw on value systems embedded in Wake up to Wogan and the text of Terry Wogan as a radio personality. TOGs distance themselves from the label of ‘fandom’ as a resistance both to negative stereotypes and to the branding strategies — the textual ‘overflow’ — of media convergence. Reprinted by permission of the publisher.